2019
DOI: 10.1051/matecconf/201930404002
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation in Aeronautics through the ICARUS Aviation Data and Intelligence Marketplace

Abstract: Today, digital transformation has drifted all industries with its proven capacity to improve operations and boost revenues while building a value chain ecosystem. The aeronautics ecosystem is almost unanimously invested in some way into a digital transformation strategy in which data typically plays an instrumental role. However, despite the vast quantity of data across myriad parameters that never stop flowing across the aircraft-passengers-luggage-cargo journeys, the aviation-related stakeholders are still a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In terms of digital transformation of conventional businesses, airline companies have overtime been pushed to modify marketing strategies in order to increase their efficiency, performance and competitive advantage in the fast growing low-cost airline market (Cento, 2008). Lampathaki et al (2019) study on digital transformation in aviation data and intelligence marketplace found that digitalisation is a thriving trend in the aviation sector with about 58% of airlines forming digital strategies. The study therefore concludes that technology innovation through data platforms has the potential of accelerating digital transformation in the airline industry thus allowing companies to leverage on its benefits.…”
Section: Digitalisation In the Airline Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of digital transformation of conventional businesses, airline companies have overtime been pushed to modify marketing strategies in order to increase their efficiency, performance and competitive advantage in the fast growing low-cost airline market (Cento, 2008). Lampathaki et al (2019) study on digital transformation in aviation data and intelligence marketplace found that digitalisation is a thriving trend in the aviation sector with about 58% of airlines forming digital strategies. The study therefore concludes that technology innovation through data platforms has the potential of accelerating digital transformation in the airline industry thus allowing companies to leverage on its benefits.…”
Section: Digitalisation In the Airline Industrymentioning
confidence: 99%
“…For instance, Karaagaoglu and Çiçek (2019) posit that the ultimate goal of improving digital processes in the airline sector is improved performance and profitability. The position reinforced by Lampathaki et al (2019) that airlines can improve operational efficiency and reduce costs through digital transformation.…”
Section: Introductionmentioning
confidence: 99%